Additional records of the genus Acropimpla townes (Hymenoptera: Ichneumonidae: Pimplinae) from Vietnam and an updated key to species - Nhi, Pham Thi (Academia Journal of Biology, 2020)
Two species of the genus Acropimpla, viz. A. bicarinata (Cameron) and A. uchidai (Cushman), are recorded for the first time from Vietnam. An updated,  illustrated key to all eight Vietnamese species of Acropimpla is provided.